Do Brief Alcohol Motivational Interventions Work Like We Think They Do?. (11th October 2013) - Bertholet, Nicolas; Palfai, Tibor; Gaume, Jacques; Daeppen, Jean‐Bernard; Saitz, Richard
<x xml:space="preserve">Abstract</x> Background Questions remain about how brief motivational interventions (BMIs) for unhealthy alcohol use work, and addressing these questions may be important for improving their efficacy. Therefore, we assessed the effects of various characteristics of BMIs on drinking outcomes across 3 randomized controlled trials (RCTs). Methods Audio recordings of 314 BMIs were coded. We used the global rating scales of the Motivational Interviewing Skills Code (MISC) 2.1: counselor's acceptance, empathy, and motivational interviewing (MI) spirit, and patient's self‐exploration were rated. MI proficiency was defined as counselor's rating scale scores ≥5. We also used the structure, confrontation, and advice subscale scores of the Therapy Process Rating Scale and the Working Alliance Inventory. We examined these process characteristics in interventions across 1 U.S. RCT of middle‐aged medical inpatients with unhealthy alcohol use (n = 124) and 2 Swiss RCTs of young men with binge drinking in a nonclinical setting: Swiss‐one (n = 62) and Swiss‐two (n = 128). We assessed the associations between these characteristics and drinks/d reported by participants 3 to 6 months after study entry. Results In all 3 RCTs, mean MISC counselor's rating scales scores were consistent with MI proficiency. In overdispersed Poisson regression models, most BMI characteristics were not significantly associated with drinks/d in follow‐up. In the U.S. RCT, confrontation and self‐exploration were associated with more drinking. Giving advice was significantly associated with less drinking in the Swiss‐one RCT. Contrary to expectations, MI spirit was not consistently associated with drinking across studies. Conclusions Across different populations and settings, intervention characteristics viewed as central to efficacious BMIs were neither robust nor consistent predictors of drinking outcome. Although there may be alternative reasons why the level of MI processes was not predictive of outcomes in these studies (limited variability in scores), efforts to understand what makes BMIs efficacious may require attention to factors beyond intervention process characteristics typically examined.